Consistency improvement and normalisations in multi-criteria decision support methods - Albert, Judit; Takács, Ágnes (Design of Machines and Structures, 2025)
Optimisation problems in mechanical engineering often involve several conflicting objectives and require multi-purpose optimisation (MOO) to solve. The solution of MOO problems is a set of equally good optimal solutions, which are called Pareto-optimal solutions. In order to choose one of the Pareto-optimal solutions, multi-criteria decision-making (MCDM) is required.